Combined Intra- and Extra-Articular Technique in Revision Anterior Cruciate Ligament Reconstruction - Zanovello, Jessica; Rosso, Federica; Bistolfi, Alessandro; Rossi, Roberto; Castoldi, Filippo (Joints, 2017)
Purpose The aim of the study was to evaluate the “over the top” (OTT) nonanatomical technique for revision of anterior cruciate ligament (ACL) reconstruction.Methods Twenty-four patients with a mean age of 31.9 ± 11.2 years underwent revision of ACL reconstruction using OTT technique. International Knee Documentation Committee (IKDC) score, Knee Injury and Osteoarthritis Outcome Score (KOOS), Lysholm score, Tegner score, Subjective Patient Outcome for Return to Sport (SPORTS) score, Anterior Cruciate Ligament-Return to Sport After Injury (ACL-RSI) scale, and KT-1000 evaluation were recorded at a mean follow-up of 30.7 ± 18.9 months.Results Postoperatively, the IKDC objective total score significantly improved (p = 0.0046). The KOOS, Lysholm, and Tegner scores also improved, but the results were not statistically significant (62.4 vs. 72.6, 6.5 vs. 75.8, and 4.1 vs. 6.0, respectively). The subjective IKDC evaluation score improved from an average of 51.1 points to 63.7 points at the last follow-up (p = 0.0027). The RTP prevalence was 81.8%, with 44.4% of the patients returning to the same preinjury level. According to the SPORTS score, 16.6% of patients played sport without limitations in activity and performance. The average ACL-RSI score was 52.1 ± 27.0. No major complications were reported. A total of 21.5% of patients underwent surgical removal of staples. The failure prevalence was 14.3% and the cumulative survivorship, calculated using the Kaplan–Meier method, was equal to 70% at 60 months of follow-up.Conclusion The OTT technique in the revision ACL reconstruction provided improvement in objective and subjective scores, good RTP prevalence, and acceptable rate of complication and failure. One of the advantages was the possibility to avoid the femoral tunnel.Level of Evidence Level IV, therapeutic case series.
Keywords: anterior cruciate ligament; over the top; revision